Lunate Fracture Morphology in Kienbock's Disease—A Computed Tomography Study - MacLean, Simon B. M.; Bain, Gregory I. (Journal of Wrist Surgery, 2022)
Background The pathogenesis of Kienbock's disease is poorly understood. The coronal fracture line is acknowledged as a poor prognostic marker in the disease. Other fracture types in the Kienbock's wrist have subsequently been identified.Questions/Purposes The aim is to study the fracture morphology of the lunate in a cohort of patients using computed tomography.Methods Patient images were acquired using a set protocol with four-dimensional computed tomography scanning. Images were reviewed by two orthopaedic surgeons and a consultant radiologist. Static and dynamic images were assessed and a fracture map created. The relationship of fracture type to other parameters was then analyzed.Results Twenty-three patients were included in the study, including 11 males and 12 females, with a mean age of 43 years. Total frequency of fracture lines in the cohort was coronal – 26, proximal subchondral bone plate type – 24, avulsion – 19, sagittal – 16, and distal subchondral bone plate type – 11. There were statistically significantly more proximal than distal subchondral bone plate fractures (p = 0.03), and more coronal fractures than distal subchondral bone plate fractures (p = 0.01). There were statistically significantly more radiolunate ligament-avulsion types (p <0.001) than other types. The sagittal fracture line through the lunate approximated closely to the ulnar edge of the capitate and the ulnar edge of the radius.Conclusion Study on the fracture morphology in the Kienbock's wrist has improved our understanding of the disease pathogenesis. Fracture lines may correspond to loading points, intrinsic and extrinsic ligament avulsions. These fracture types may play a role in disease progression and are important to identify when considering lunate salvage surgery.
Keywords: Kienbock's disease; fracture; 4D-CT; pathogenesis; lunate